Entrepreneurship, Professionalism and Leadership Intention of Generation Z: The Case of Kahta - Gulsen Kirpik (SEISENSE (PRIVATE) LIMITED, 2020)
Aim - This study aims to measure the level of entrepreneurship, professionalism, and leadership intention of the Z generation. This effort is to investigate whether the socio-demographic characteristics of the Z generation, such as gender, education level, work experience, family income level, the presence of entrepreneurs in the family, or the immediate vicinity, leading to significant differences on the levels of entrepreneurship, professionalism and leadership intention. Methodology – The simple random sampling method was used to collect data. A total of 563 questionnaires was collected for the study. The participants were mainly the students in high schools and vocational schools of higher education in the Adiyaman-Kahta district. SPSS 22.0 program was used to analyze the data set. Findings - Cronbach's alpha value of the scale of entrepreneurship, professionalism, and leadership intention was measured as 0.89. Moreover, non-parametric analysis methods were used to test the hypotheses of the study because the data did not show normal distribution (p <0.01). The hypotheses were analyzed with Mann-Whitney U and Kruskal Wallis H tests. Originality – The study will help the policymakers to develop projects and training programs to promote entrepreneurship in the generation Z and following generations.